2023
DOI: 10.3390/ijerph20247171
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Knowledge Deficit in Hospital Bed Planning and Defining an Optimum Region for the Number of Different Types of Hospital Beds in an Effective Health Care System

Rodney P. Jones

Abstract: Based upon 30-years of research by the author, a new approach to hospital bed planning and international benchmarking is proposed. The number of hospital beds per 1000 people is commonly used to compare international bed numbers. This method is flawed because it does not consider population age structure or the effect of nearness-to-death on hospital utilization. Deaths are also serving as a proxy for wider bed demand arising from undetected outbreaks of 3000 species of human pathogens. To remedy this problem,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
49
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(53 citation statements)
references
References 117 publications
4
49
0
Order By: Relevance
“…This has resulted in over 300 publications on these topics and the related issue of financial risk in healthcare purchasing. To avoid self-citation these papers can be found in the Supplementary file (https://www.mdpi.com/1660-4601/20/24/7171/s1) of a recent review of internationally available bed supply [1]. These publications are split into 19 alphabetical sections with numbered papers in each section, hence, publication L.1.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…This has resulted in over 300 publications on these topics and the related issue of financial risk in healthcare purchasing. To avoid self-citation these papers can be found in the Supplementary file (https://www.mdpi.com/1660-4601/20/24/7171/s1) of a recent review of internationally available bed supply [1]. These publications are split into 19 alphabetical sections with numbered papers in each section, hence, publication L.1.…”
Section: Introductionmentioning
confidence: 99%
“…The review concluded that a new model could be applied, which plots the ratio of available beds per 1,000 deaths against the natural log of the number of deaths per 1,000 population [1]. The ratio of deaths per 1,000 population is used to approximate the population age structure.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations